Transnasionalisme Islam Indonesia; Studi Gerakan Keagamaan Fundamentalis Komunitas Wanita Bercadar di Kecamatan Pace Kabupaten Nganjuk - Mukhamat Saini (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2018)
Community veiled women in this study is a group of women who are Muslims by using Muslim clothing and plus a veil to cover his face except the eyes veiled. Women here is a very important research object, this is because the woman is classified something new and attract the attention of the public then has a mystery that needs to be known more deeply, as its movement in conducting a socio-religious change in Pace Nganjuk. This research uses field study. The respondents consist of women veiled and residents in the area. Interview results from interviews conducted are used as primary data supported by secondary data. All the data collected then analyzed qualitatively and quantitatively to obtain conclusions. From the results of the study it was answered that the veiled women group had values ??that became the foundation in taking action, namely religious values ??and the value of exclusivism. Progressive veiled women have committed fundamentalist actions in the areas of religion, education and economics. Community action veiled women are able to bring changes in the socio-religious community Pace Nganjuk. The change can be seen from the increase of women who wear the veil in daily activities in the community.